2015
DOI: 10.1371/journal.pone.0119886
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Transmitted HIV-1 Gag HLA Class I-Driven Immune Escape Variants but Minimal Immune Selection over the First Year of Clade C Infection

Abstract: In chronic HIV infection, CD8+ T cell responses to Gag are associated with lower viral loads, but longitudinal studies of HLA-restricted CD8+ T cell-driven selection pressure in Gag from the time of acute infection are limited. In this study we examined Gag sequence evolution over the first year of infection in 22 patients identified prior to seroconversion. A total of 310 and 337 full-length Gag sequences from the earliest available samples (median = 14 days after infection [Fiebig stage I/II]) and at one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 87 publications
3
16
0
Order By: Relevance
“…Since CTL escape mutations in key Gag epitopes have been linked to lower viral replication capacity (7,8,18,(28)(29)(30)(31)(32)40), the numbers of these mutations in paired mother-infant sequences were compared. It was observed that Gag epitope escape mutations were frequently transmitted, as has been reported in studies of viruses from early HIV-1 infection in adults (8,19,37), but overall, infant-derived viruses had fewer Gag epitope escape mutations than did viruses from the mothers, and therefore, the frequency of these mutations did not explain the difference in replication capacities between mothers and their infants. We also investigated the hypothesis that early escape in the infant-derived viruses was driving the lower replication capacity by analyzing sequences for HLA-associated footprints in Gag, but we found no evidence that this was the case.…”
Section: Figmentioning
confidence: 64%
See 1 more Smart Citation
“…Since CTL escape mutations in key Gag epitopes have been linked to lower viral replication capacity (7,8,18,(28)(29)(30)(31)(32)40), the numbers of these mutations in paired mother-infant sequences were compared. It was observed that Gag epitope escape mutations were frequently transmitted, as has been reported in studies of viruses from early HIV-1 infection in adults (8,19,37), but overall, infant-derived viruses had fewer Gag epitope escape mutations than did viruses from the mothers, and therefore, the frequency of these mutations did not explain the difference in replication capacities between mothers and their infants. We also investigated the hypothesis that early escape in the infant-derived viruses was driving the lower replication capacity by analyzing sequences for HLA-associated footprints in Gag, but we found no evidence that this was the case.…”
Section: Figmentioning
confidence: 64%
“…The pNL4-3Δgag-protease plasmid was generated (52) and prepared (18) as described previously. Ten micrograms of BstEII-digested pNL4-3Δgag-protease and ϳ80 l of the gag-protease PCR product were cotransfected into 2.5 million CEM-GXR25 cells (GXR cells) (60) in 800 l R10 medium via electroporation at 300 V and 500 F (18,37). The electroporated cells were allowed to recover for 1 h before the contents of each cuvette were transferred to 25-cm 2 flasks containing 4 ml medium.…”
Section: Methodsmentioning
confidence: 99%
“…However, the high rate of non-synonymous substitutions outside the HIV_gagconsv epitopes implies that escape mutants outside the HIV_gagconsv are more likely to be integrated into the HIV-1 latent cellular reservoir landscape. This is because latent reservoir strains are established during the early stages of infection and are known to compose majorly of CTL immune escape strains ( Deng et al, 2014 ; Gounder et al, 2015 ; Roberts et al, 2015 ; Leitman et al, 2017 ). Therefore, these latent reservoirs may require a broad CTL response for clearance, as previously alluded to Deng et al (2014) .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the viral set point more accurately, we also defined the long-term chronic set point as the median of all pre-ART viral loads available as (1) including the diagnostic (acute) measurement, (2) excluding the diagnostic measurement, (3) including all measurements from >2 weeks after diagnosis, (4) including all measurements from >1 month after diagnosis, or (5) including all measurements from >3 months after diagnosis. Chronic set points were very similar irrespective of the definition, and results using definition 4 are reported here because this may most accurately reflect the beginning of the chronic phase [ 21 , 22 ]. Set-point differences between vaccinees and placebo recipients were analyzed using the Mann–Whitney U test (Prism v5.0c).…”
Section: Methodsmentioning
confidence: 99%